Clinical diagnostic decision-making in real life contexts: A trans-theoretical approach for teaching: AMEE Guide No. 95. (March 2015) - Patel, Rakesh; Sandars, John; Carr, Sue
Abstract Making an accurate clinical diagnosis is an essential skill for all medical students and doctors, with important implications for patient safety. Current approaches for teaching how to make a clinical diagnosis tend to lack the complexity that faces clinicians in real-life contexts. In this Guide, we propose a new trans-theoretical model for teaching how to make an appropriate clinical diagnosis that can be used by teachers as an additional technique to their current approach. This educational model integrates situativity theory, dual-information processing theory and socio-cognitive theory. Mapping and microanalysis help the teacher to identify the main processes involved in making an accurate clinical diagnosis, so that feedback can be provided that is focused on improving key aspects of the skill. An essential aspect of using the new educational model is the role of the experienced clinical teacher in making judgments about the appropriateness of the learner's attempts to make a clinical diagnosis.